1997
DOI: 10.2307/3053983
|View full text |Cite
|
Sign up to set email alerts
|

Just Des(s)erts? The Racial Polarization of Perceptions of Criminal Injustice

Abstract: Sociologists have long been interested in how reactions to deviance influence social order and consensus. However, classic statements on this subject present contrasting hypotheses. This article extends previous work by examining how the extensive media coverage of an interracial homicide influences public attitudes toward the criminal justice system. Initial results indicate that race, education, and police contact directly effect perceptions of criminal injustice. Perceptions of injustice are especially high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 63 publications
5
115
0
3
Order By: Relevance
“…It could be argued that a focus on death sentence cases featuring an interracial element, which were rare during this time period, is an effort to sensationalize such incidents. However, since death sentences involving white defendants (constituting the majority of death sentences) were also more likely to be covered by the Plain Dealer, it casts a shadow over the previous assumption, presumably since black offender-white victim homicides would be considered more newsworthy (see Wortley, Hagan, and MacMillan, 1997). Although previous research has shown a race of defendant or race of victim effect regarding media coverage of homicides and other crimes (see generally, Sorenson, Manz, and Berk, 1998;Johnstone, Hawkins, and Michener, 1994), the narrow focus of this study (homicides that resulted in a death sentence) may have played a role in the non-significant results for these variables.…”
Section: Resultsmentioning
confidence: 99%
“…It could be argued that a focus on death sentence cases featuring an interracial element, which were rare during this time period, is an effort to sensationalize such incidents. However, since death sentences involving white defendants (constituting the majority of death sentences) were also more likely to be covered by the Plain Dealer, it casts a shadow over the previous assumption, presumably since black offender-white victim homicides would be considered more newsworthy (see Wortley, Hagan, and MacMillan, 1997). Although previous research has shown a race of defendant or race of victim effect regarding media coverage of homicides and other crimes (see generally, Sorenson, Manz, and Berk, 1998;Johnstone, Hawkins, and Michener, 1994), the narrow focus of this study (homicides that resulted in a death sentence) may have played a role in the non-significant results for these variables.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Jamaican crime, in these 1992 articles, is taken to be confined to violent crime, so that the picture that emerges from the 1992 articles is indeed similar to the one we find in 1994. It is also clear that the 1992 discussion was part of a much wider and more longstanding tendency to criminalize racialized "minorities" in general, and Jamaican Canadians in particular, in the media: a criminalization that results in discriminatory treatment at the personal level (as documented in Wortley, Hagan, & Macmillan 1997; see also Makin, 1994), and that is reflected in research conducted over many years and across several disciplines (Mirchandanai & Chan, 2002) But what was apparently new to Toronto in 1994, and which proved to be the key factor co-ordinating the re-institution of the identity of the Jamaican criminal, was the introduction of a specific program for re-orienting our discursive and non-discursive conduct in relation to its problematic individuality. This program was widely embraced for a time, although it only ever partially took hold outside of the police department, and from the beginning drew criticism from some commentators (DiManno, 1994b) and citizens (Makin, 1994).…”
Section: Two Models Of Crime and Criminal-law Enforcementmentioning
confidence: 99%
“…Perhaps more disconcerting is the fact that many Anglos perceive no racial or ethnic bias in the system, so that they insulate themselves from difficult questions of how to eliminate it. Twice as many blacks and Latinos (56 percent of both) as European Americans (27 percent) agree that the police in their community treat one or more racial groups unfairly (BJS, 2004: (Hurwitz and Peffley 2001); (Wortley, Hagan and Macmillan 1997)). Most persuasively, asked simply whether "the opportunity for equal justice under the law is equal for blacks and whites," half of whites, compared with a third of Latinos and only a seventh of blacks, said yes.…”
Section: White Ambivalence About Equalitymentioning
confidence: 99%